Efficacy of intralesional triamcinolone injection in the management of benign refractory esophageal strictures - Narayanan, Lavanya; Mohamed, Kani Shaikh; A. R., Akilandeswari; A., Anand; N., Arun (International Journal of Research in Medical Sciences, 2022)
Background: Endoscopic therapy is the mainstay in the treatment of esophageal strictures. Refractory strictures are difficult to treat with patients requiring frequent endoscopic therapy. Intralesional steroid injection combined with SG dilation has been reported to reduce the frequency of endoscopic dilation in such cases. Methods: Ten patients with benign esophageal strictures (corrosive 4, peptic 2, anastomotic 2, radiation-induced 2) were selected for this study. All of them had refractory esophageal stricture. They were being managed with intermittent endoscopic dilation by using Savary Gilliard dilators. All patients were treated by intralesional injections of triamcinolone acetonide 40 mg in a 4-quadrant fashion after SG dilation and were followed up for a period of 1 years. At each session, SG dilation was done followed by 4 injections (4 quadrants) at the proximal margin of the stricture. The interval between dilations and frequency of dilations were calculated before and after triamcinolone injections. A periodic dilation index (PDI) (number of dilations per month) before and after the triamcinolone injections was calculated. Results: The PDI decreased significantly from 1.7 before injection to 0.6 after injection. This effect was seen irrespective of the etiology of the stricture involved. Conclusions: Intralesional triamcinolone therapy is a useful and effective therapy for symptom relief in benign refractory esophageal strictures.